BURUNG SEBAGAI ATRAKSI EKOWISATA DI KAWASAN PARIWISATA UBUD, BALI - Dalem, A.A.G Raka; Widana, I N; Putri, I.A Trisna Eka (Environmental Research Center (PPLH) of Udayana University, 2016)
ResearchÂ on â€œBirds as an Ecotour Attraction in Ubud Tourist Resort, Baliâ€ (Burung sebagaiAtraksi Ekowisata di Kawasan Pariwisata Ubud, Bali) was undertaken in 2013. Aims ofthese research were as follows: first, to find out birds observed in Ubud Tourist Resort, Baliand second, to find out their potentials as ecotour attractions.Samples were collected by exploring the study sites and running interview between July andOctober, 2013.Â Observation was carried out by using binoculars and number of individualsof birds was counted by using a counter when necessary.Â Birds were identified such asthrough direct observation on the species, or through their calling.Â Results of observationwere compared with hand boooks, such as Mackinnon (1990) and Mackinnon et al. (1992).Birds data were recorded either on their species and on numbers (relative)/freqency, and theresult was typed in tables.Â The data provided such as the status (protected/not), migrantspecies or not, as well as their distribution.Â In addition, locations where birds have beenused as a tour attraction (ecotour attraction - bird watching), and how to set up theirproducts were reported.From this research it can be concluded as follows.Â In Ubud tourist resort at least 67 birdspecies have been identified, in which 7 (seven) were birds that were restricted theirdistribution in Indonesia, namely:Â Halcyon cyanoventris, Alcedo caerulescens, Paddaoryzivora, Prinia familiaris, Treron griseicauda, Dicaeum trochileum, and Gallus varius.In addition, from this reserach it was observed seven species of migrating birds: Hirundorustica, Merops philippinus or M. superciliosus, Accipiter soloensis, Actitis hypoleucos,Tringa glareola, Gallinago stenura, and Apus pacificus.From all birds observed, there were 14 species that were classified as protected species inIndonesia, namely: Sturnus melanopterus, Anhinga melanogaster, Bubulcus ibis, Egrettaalba, Egretta garzatta, Egretta intermedia, Halcyon cyanoventris, Halcyon chloris, Alcedocaerulescens, Haliastur indus, ...